Evaluating the Impact of Oral Contraceptives on Pancreatic Cancer Risk: A Two-Sample Mendelian Randomization Analysis - Yuxin Tang; Yu Zhang; Shuaiyi Wang; Xinyi Shi; Xinjia Ruan; Yu Cheng; Fangrong Yan; Tiantian Liu (Biomedicines, 2025)
Background: The relationship between oral contraceptive (OC) use and pancreatic cancer (PC) risk remains controversial, with inconsistent findings reported in observational studies. To clarify this relationship and better identify potential risk factors for PC prevention, more unbiased and robust approaches are needed. Methods: We investigated the potential causal relationship between OC use and PC risk using a two-sample Mendelian randomization (MR) analysis, with blood protein quantitative trait loci (pQTLs) as instrumental variables. To ensure the robustness of our findings, we performed a series of sensitivity analyses, colocalization analyses, and reverse MR. The causal effects of protein-coding genes on PC risk, as well as their expression patterns across different single-cell types, were subsequently investigated. To elucidate the potential pathogenic pathways, we conducted pathway enrichment analysis, protein–protein interaction (PPI) network analysis, and causal inference. Results: Our MR analysis identified five drug-targeted proteins significantly associated with PC risk. Higher levels of COMT, AGT, FN1, and UGT1A1, as well as lower levels of SERPINC1, were associated with an increased risk of PC. Among these, AGT, FN1, and COMT demonstrated consistent associations across sensitivity analyses and downstream analyses, providing robust evidence supporting their involvement in PC risk. Conclusions: This study provides genetic evidence suggesting, in European groups, a potential causal link between OC use and increased PC risk, possibly mediated through drug-targeted proteins such as AGT and FN1. These results highlight the importance for further research to elucidate the underlying mechanisms and assess the implications of OC use on PC risk.